2015
DOI: 10.1002/lno.10028
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic identity and phytoplankton diet affect fatty acid composition of zooplankton in large lakes with differing dissolved organic carbon concentration

Abstract: An increase in loading of dissolved organic carbon (DOC) from terrestrial to freshwater ecosystems has recently been documented in several boreal regions. We studied how transfer of important biomolecules, fatty acids, may be connected to DOC in pelagic food webs of large boreal lakes. We collected nine zooplankton taxa during three seasons from six lakes along a gradient of DOC (5-10 mg C L 21 ). Taxonomic identity explained 62% of the variation in zooplankton fatty acids, while the effects of DOC and season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 63 publications
7
46
0
Order By: Relevance
“…Our previous research (Hiltunen, Strandberg, Keinänen, Taipale, & Kankaala, 2014;Hiltunen et al, 2015) shows that these fatty acids are generally only found in L. macrurus, and not in other zooplankton taxa or seston. Our previous research (Hiltunen, Strandberg, Keinänen, Taipale, & Kankaala, 2014;Hiltunen et al, 2015) shows that these fatty acids are generally only found in L. macrurus, and not in other zooplankton taxa or seston.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our previous research (Hiltunen, Strandberg, Keinänen, Taipale, & Kankaala, 2014;Hiltunen et al, 2015) shows that these fatty acids are generally only found in L. macrurus, and not in other zooplankton taxa or seston. Our previous research (Hiltunen, Strandberg, Keinänen, Taipale, & Kankaala, 2014;Hiltunen et al, 2015) shows that these fatty acids are generally only found in L. macrurus, and not in other zooplankton taxa or seston.…”
Section: Discussionmentioning
confidence: 91%
“…vertical profiles of oxygen, chlorophyll, and light) are available from authors and in the study byHiltunen et al (2015) More environmental information on the study lake (e.g.…”
mentioning
confidence: 99%
“…Differences in the FA composition of seston (primary producers, heterotrophic bacteria and small heterotrophic flagellates), different zooplankton groups and fish were significant, and the taxonomic grouping explained~72% of the observed variation in the FA composition of the pelagic food web (PERMANOVA Pseudo-F 9,305 = 80.588, P = 0.001). The remaining variation is likely due to seasonal and spatial differences in the FA composition (see Hiltunen et al, 2015;Strandberg et al, 2015 for details). The PUFA with the highest effect on the sample ordination were DHA and ALA.…”
Section: Resultsmentioning
confidence: 98%
“…Vendace are known to feed extensively on both cladocerans and copepods (Viljanen, 1983;Northcote and Hammar, 2006), presumably also in our study area since the δ 15 N of vendace should be higher if they solely consumed copepods. However, it is well established that cladocerans contain very little DHA, while freshwater copepods in general are rich in DHA (Persson and Vrede, 2006;Smyntek et al, 2008;Ravet et al, 2010;Burns et al, 2011;Hiltunen et al, 2015). Elongation and desaturation of shorter chained analogs (C 18 PUFA or EPA) could account for the high proportion of DHA in vendace.…”
Section: Tablementioning
confidence: 98%
See 1 more Smart Citation